Cover Feature: Structural Diversity and Anticancer Activity of Marine‐Derived Elastase Inhibitors: Key Features and Mechanisms Mediating the Antimetastatic Effects in Invasive Breast Cancer (ChemBioChem 8/2018). (23rd March 2018) - Al‐Awadhi, Fatma H.; Paul, Valerie J.; Luesch, Hendrik
Abstract : The cover feature picture shows cyclodepsipeptides, the producing marine cyanobacterium overgrowing a coral, and the compounds' anticancer effects. Cyclodepsipeptides inhibit human neutrophil elastase and, as a consequence, the migration of invasive breast cancer cells through the modulation of gene expression and proteolytic processing of membrane proteins. More information can be found in the full paper by H. Luesch et al. onpage 815 in Issue 8, 2018 (DOI:10.1002/cbic.201700627 ).